Pengaruh Inflasi, PDB, ROA Perusahaan Sektor Pertanian, Kehutanan, Perikanan Terdaftar di BEI Terhadap Investasi Asing Langsung di Indonesia Periode 2008-2022 - Halim, Abdul (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to look at the short-term and long-term relationship between variables inflation, Gross Domestic Product and Return on Assets sector companies of agricultural, forestry and fisheries listed on the Indonesian Stock Exchange on Foreign Direct Investment in Indonesian period 2008 to 2022. One of the reason for choosing this sector because this sector absorbs the largest workforce during period 2020 to 2022. With the number of workers in 2022 amounting to 38.7 million people. This research uses quantitative methods with panel data type and data sources from the Central Bureau of Statistics, Bank Indonesian, Ministry of Trade, and ESG Intelligence. Using the analysis method Panel Vector Error Correction Model. Based on the results show that the short-term inflation variable has a positive effect and the long-term has negative effect on Foreign Direct Investment in Indonesian. The Gross Domestic Product variable has no effect in the short and long term on Foreign Direct Investment in Indonesian. The Return on Assets variable has negative effect in the short term and positive effect in the long term on Foreign Direct Investment in Indonesian.